Phytochemical profile and hepatoprotective activity of Moringa oleifera Lam leaf extract in acetaminophen-challenged mice - Yong, Yoong Soon; Siao, Michelle; Ng, Kam Heng; Ng, Boon Ful; Tan, Jen Kit; Mohd Nasir, Nurul Fatimah; Tan, Wen Siang; Alitheen, Noorjahan Banu; Yeap, Swee Keong; Yong, Chean Yeah (Elsevier Ltd, 2026)
Moringa oleifera leaves are rich in phytochemicals, including flavonoids and polyphenols, with reported antioxidant and hepatoprotective properties. This study evaluated the phytochemical profile of an aqueous-ethanolic extract and its efficacy against acetaminophen (APAP)-induced hepatotoxicity in mice. LC-MS/MS identified 80 metabolites, mainly flavonoids and amino acids. The extract showed moderate antioxidant activity in DPPH and FRAP assays, with a total phenolic and total flavonoid contents of 24.73 mg GAE/g DW and 2.95 mg CE/g DW, respectively. In vivo, mice given toxic APAP doses and treated with the extract (50 or 200 mg/kg) exhibited improved liver histology, reduced serum ALT and AST, suppressed CYP2E1 activity, and restored glutathione levels. Proinflammatory cytokines (IL-1α, IL-1β, IL-6, MIP-1α, MCP-1, TNF-α) and hepatic iNOS and NF-κB expression were also downregulated. Additionally, liver metabolomics revealed normalization of lipid metabolism and prostaglandin levels. These findings suggest that M. oleifera extract confers hepatoprotection via antioxidant, anti-inflammatory, and metabolic pathways, supporting its potential in functional food and nutraceutical applications.